Seasonal changes in physical performance and heart rate variability in high level futsal players - Oliveira, R. S.; Leicht, A. S.; Bishop, D.; Barbero-Alvarez, J. C.; Nakamura, F. Y. (International Journal of Sports Medicine, 2013)
The aim of this study was to determine the changes in physical performance and resting heart rate variability (HRV) in professional futsal players during the pre-season and in-season training periods. 11 athletes took part in the study (age=24.3±2.9 years; height=176.3±5.2 cm; weight=76.1±6.3 kg), and performed a repeated-sprint ability (RSA) test [6×40 m (20+20 m with a 180° change of direction) sprints separated by 20 s of passive recovery] and Yo-Yo intermittent recovery test level 1 (Yo-Yo IR1) at 3 different moments (M1=beginning of pre-season; M2=end of pre-season; M3=mid in-season). The HRV indices were assessed at the same moments. After the short pre-season (3-week), mean RSA time (RSAmean) (M1=7.43±0.2 s; M2=7.24±0.2 s; P=0.003), decrement in RSA performance (RSAdecrement) (M1=6.7±0.3%; M2=5.0±0.9%; P=0.001), and Yo-Yo IR1 distance (M1=1.244±298 m; M2=1.491±396 m; P=0.002) were significantly improved (P<0.05). During the in-season (i. e., M3), performance in Yo-Yo IR1 and RSAmean were maintained. In contrast, RSAbest (M2=6.89±0.2 to M3=6.69±0.3; P=0.001) was improved and RSAdecrement (M2=5.0±0.9% to M3=6.6±0.9%; P=0.001) was impaired. At M2, there was an increase in HRV vagal-related indices compared with M1 that was maintained at M3. In conclusion, after a short pre-season, futsal players improved their RSA and Yo-Yo IR1 performance with concomitant improvements in HRV. These indices were maintained during the in-season period while RSAbest was improved and RSAdecrement impaired. Frequent monitoring of these performances and HRV indices may assist with identification of individual training adaptations and/or early signs of maladaption.